Cytotoxic evaluation of 6-metoxy tetrahydro-β-carboline derivatives (6mthβc) in human neuroblastoma (sk-n-sh) cells - Mohamed, Siti Mazleena; Ezzat, Mohammed Oday; Mordi, Mohd Nizam (2025)
Tetrahydro-β-carboline (THβC) alkaloids, a varied group of indole-derived chemicals, demonstrate pharmacological actions including anticancer, antibacterial, antioxidant, and neuroactive effects in nature. In this study, 6-methoxy-tetrahydro-β-carboline (6MTHβC) has been synthesized and evaluated for its toxicity against the human neuroblastoma cell line (SK-N-SH) using the MTT assay. The assay was conducted at a concentration of 50 μM of each compound. The findings showed that four compounds exhibited toxicity toward SK-N-SH cells, while eight compounds demonstrated more than 50% cell viability. This study provides fundamental toxicological insights into these compounds and lays the groundwork for pharmacological and potential new treatment possibilities related to neurodegenerative disease.